Basidiobolomycosis in a 14-year-old girl. - Sulaksanaswastho, Suyoso; Maylita, Sari; Linda, Astari; Evy, Ervianti; Sunarso, Suyoso; Raniah, Baswedan (European Journal of Pediatric Dermatology, 2025)
Basidiobolomycosis is a rare subcutaneous fungal infection caused by Basidiobolus ranarum, typically affecting children and young males in tropical regions. Its clinical presentation is nonspecific and often mimics other granulomatous or infectious conditions, leading to frequent misdiagnosis. We report the case of a 14-year-old girl who presented with a firm, erythematous mass on the right thigh that progressively increased in size. Histopathological examination revealed fungal hyphae surrounded by the Splendore-Hoeppli phenomenon, and fungal culture confirmed the presence of B. ranarum. This case highlights the importance of considering basidiobolomycosis in the differential diagnosis of chronic subcutaneous lesions in endemic areas.